Activist with opt-outs: Denmark, the European Union and the American world order - Wivel, Anders (Politica, 2017)
Is Danish European policy activist? Danish European policy is surprisingly activist in the sense that it strategically, independently and boldly pursues the defense and promotion of Danish interests and values, even to the extent of defying the vision of Europe promoted by EU’s Franco-German engine. However, activism is typically formulated by Danish decision makers as the “politics of necessity” combining a pragmatic defense of the Danish welfare state with proactive agenda-setting in selected issue areas. Using a neoclassical realist explanatory model, the article explains this policy as a the result of policy makers grounded in a Danish liberal-egalitarian political culture navigating an international space characterized by a combination of an American liberal order and negotiated and institutionalized European power politics.